2010
DOI: 10.1002/jhet.456
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of 3,4‐dihydro‐2H‐pyran with oxalyl chloride: Formation and crystal structure analysis of an unexpected bicyclic product

Abstract: in Wiley Online Library (wileyonlinelibrary.com).3,4-Dihydro-2-H-pyran and oxalyl chloride react, depending on the conditions, to keto esters, a pyran-3-carboxylic acid or derivatives thereof, or to an hitherto unknown bicyclic acetal containing a vinyl chloride moiety. The structure of the latter product has been unambiguously elucidated by single-crystal X-ray structure analysis. A mechanism for its formation is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Despite potential biological properties, only two synthetic methods have been documented in the literature to construct furo­[2,3- b ]­pyran scaffolds. Flower et al reported a protocol of TiCl 4 mediated addition of 3,4-dihydro-2 H -pyran to (2-trimethylsilyl)-ethyl pyruvate, which results in perhydro­[2,3- b ]­pyran derivatives, while Schmidt condensed 3,4-dihydro-2 H -pyran with oxalyl chloride, to give the 2-chloro variant in MeOH at an elevated temperature of 120 °C in 42% yield . However, these two reports were limited to a single example in each case.…”
mentioning
confidence: 99%
“…Despite potential biological properties, only two synthetic methods have been documented in the literature to construct furo­[2,3- b ]­pyran scaffolds. Flower et al reported a protocol of TiCl 4 mediated addition of 3,4-dihydro-2 H -pyran to (2-trimethylsilyl)-ethyl pyruvate, which results in perhydro­[2,3- b ]­pyran derivatives, while Schmidt condensed 3,4-dihydro-2 H -pyran with oxalyl chloride, to give the 2-chloro variant in MeOH at an elevated temperature of 120 °C in 42% yield . However, these two reports were limited to a single example in each case.…”
mentioning
confidence: 99%